Post-traumatic stress disorder and post-traumatic stress symptoms in parents of children with cancer: A review - Yalug, Irem; Tufan, Ali Evren; Doksat, Kerem; Yalug, Kivanc (Universitatsverlag Ulm Gmbh, 2011)
Increasing periods of survival in cancer led to an increase in observations of psychological problems in patients and their relatives, causing an increase in studies addressing the psychological effects of cancer and subsequent cure. Children with cancer may experience medical procedures as traumatic, and their caretakers/medical staff as perpetrators. Their parents have been found to report higher rates of trauma-related symptomatology. Therefore, the aim of this paper was to provide a critical review of Post-traumatic Stress Disorder (PTSD) and Post-Traumatic Stress Symptoms (PTSS) in parents of survivors of pediatric cancer and to compare the results with those reported from Turkey and Israel. PubMed search engine was used for the literature search and the results were reviewed. As a consequence of this search, it was observed that the prevalence of PTSS in parents varied between 12.0% and 80.0% while the prevalence of current PTSD in parents varied between 6.2% and 34.6%. Most of the studies assessing PTSS/PTSD in pediatric cancer survivors and their parents had small and heterogeneous samples and that most are cross-sectional in nature. Mothers may be especially affected. Educational status, living conditions and past-traumas may be important in samples from Turkey and Israel. Further studies are required to evaluate the relationship among various family members for PTSD/PTSS as well as to determine the prevalence and predictors of parental symptoms. (C) 2011 Elsevier GmbH. All rights reserved.
Keywords: Cancer; Pediatric; PTSD; Post-traumatic stress disorder; Parent; Family; Oncology; Psychooncology